To each his own Scheherazade: myth, discourse and poetics - BOUGHACHICHE, Meriem (Journal of Human Sciences, 2022)
Having become a myth, Scheherazade, whose name still resonates in our memories, is the emblematic figure of an oriental universe, symbol of a world dominated by men, representing the beautiful and adored but weak and rebellious woman, often fantasized and parodied. But what do we really know about this much desired woman, having the secret of seduction, speech and the art of storytelling? The one that gave birth to the most surprising imagery of the Eastern world. Why do we still read The Thousand and One Nights? How do we capture this feminine image? What feminine and/or feminist imagination can she draw implicitly in literature? What are its social representations? How do some refuse to be part of his lineage while others claim this filiation? This study poses the problem of the mythification and demystification of the image of an oriental woman who has become a myth through a sociopoetic approach in literary texts accounts for the functioning of a female imagination and its variations, of a discourse of Scheherazade.